A New Perspective on Classical Choice Problems Using Selection Functions - Jules Hedges; Paulo Oliva; Evguenia Winschel; Viktor Winschel; Philipp Zahn (University of Mannheim, Department of Economics, 2014)
We use quantifiers and selection functions to generalize the classical economic approach to choice. Our framework encompasses preference and utility based approaches as special cases, but also extends to non-maximizing behavior and context-dependent motives such as social concerns. We adapt the method of quantifiers and selection functions which is based on higher-order functions and originate in computer science.
urn:nbn:de:bsz:180-madoc-361799
Keywords: C0; D01; D03; D63; D64; 330; behavioral economics; social preferences; beauty contest; higher order functions; quantifiers; selection functions